"It sounds very negative": Patient perspectives on de-escalation of treatment concept and language. Issue 28 (1st October 2022) - Andrews, Courtney J.; Lawhon, Valerie; Wolff, Antonio C.; Wallner, Lauren P.; Smith, Mary Lou; Rocque, Gabrielle Betty
Abstract : 254 Background: As the combination of systemic and targeted chemotherapies is associated with severe adverse side effects and long-term health complications, there is interest in reducing treatment intensity for patients with early-stage breast cancer (EBC). Currently, this approach is being described as "de-escalation, " though there is some concern that this language and framing are not well understood or preferred by patients. Methods: We collected qualitative interview data from twenty-four patients with Stage II-III breast cancer and sixteen patient advocates. Interviews explored interest in participation in clinical trials testing reduced amounts of chemotherapy, reactions to the word "de-escalation, " and preferred ways to describe this approach and its anticipated benefits. Interviews were audio-recorded and transcribed, and researchers used qualitative content analysis to code for dominant themes. Results: Twenty-three participants (57.5%) expressed interest in participating in a trial of reduced chemotherapy. However, 60% of participants had a negative response to the word "de-escalation, " including 78% of respondents that said they were interested in the concept. To describe this approach, respondents tend to prefer words like "personalization, " "optimization, " or "reduced chemotherapy." Participants also expressed the importance of provider-patient communication, clear and simple language, sharing the decision-making process, and continued support throughout and after treatment in their consideration of trials testing lower amounts of chemotherapy. Conclusions: Among individuals with EBC, there is significant interest in alleviating treatment-related toxicity by reducing chemotherapeutic intensity. Patients are more apt to feel comfortable participating in trials testing this approach if they are framed in terms of customizing treatment to the individual patient and added benefit—reduced toxicities, higher quality of life during treatment and lower risk of long-term complications—rather than in terms of taking treatments away or doing less than the standard of care. "De-escalation" is not an ideal word to describe these trials as many associate this word with giving up in the war against cancer. Instead, participants prefer positive, patient-centered language. This information will be useful to providers in considering how best to describe de-escalation clinical trials to eligible patients in ways that avoid therapeutic misconception and facilitate the shared decision-making process regarding treatment.